A Case Report of Stroke in a Young Recreational Drug Abuser with Left Ventricular Apical Myxoma with Lupus Nephritis, Secondary Antiphospholipid Syndrome and Homocysteinemia (Bangladesh Heart Journal, 2017)
In young adults 20%-47% cases of stroke is due to cardiac embolism. Cardiac Myxoma is an infrequent cause of embolic stroke in young. We are reporting a case of a ischemic stroke in a young adult of 34 years with a history of recreational drug use who was eventually diagnosed with Left Ventricular Apical Myxoma, Systemic Lupus Erythematous (SLE), Lupus Nephritis, Secondary Anti phospholipid Syndrome, Hyper homocysteinemia, and Dyslipidemia.Bangladesh Heart Journal 2017; 32(1) : 55-61